Shannon entropy estimation for linear processes - Timothy Fortune; Hailin Sang (Journal of Risk and Financial Management, 2020)
In this paper, we estimate the Shannon entropy S(f)=-E[log(f(x))] of a one-sided linear process with probability density function f(x). We employ the integral estimator Sn(f), which utilizes the standard kernel density estimator fn(x) of f(x). We show that Sn(f) converges to S(f) almost surely and in 2 under reasonable conditions.
Keywords: 330; kernel entropy estimation; linear process; Shannon entropy